2017
DOI: 10.1038/s41541-017-0016-6
|View full text |Cite
|
Sign up to set email alerts
|

An avian influenza H7 DNA priming vaccine is safe and immunogenic in a randomized phase I clinical trial

Abstract: A novel avian influenza subtype, A/H7N9, emerged in 2013 and represents a public health threat with pandemic potential. We have previously shown that DNA vaccine priming increases the magnitude and quality of antibody responses to H5N1 monovalent inactivated boost. We now report the safety and immunogenicity of a H7 DNA-H7N9 monovalent inactivated vaccine prime-boost regimen. In this Phase 1, open label, randomized clinical trial, we evaluated three H7N9 vaccination regimens in healthy adults, with a prime-boo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 43 publications
0
38
0
Order By: Relevance
“…Among the 9 studies identified for further analysis, only six studies were, finally, identified for meta-analysis. The four trials, including three LAIV trials 20,27 and one trial with DNA-inactivated vaccine prime-boost strategy, 28 were excluded for meta-analysis. This might affect the study potency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 9 studies identified for further analysis, only six studies were, finally, identified for meta-analysis. The four trials, including three LAIV trials 20,27 and one trial with DNA-inactivated vaccine prime-boost strategy, 28 were excluded for meta-analysis. This might affect the study potency.…”
Section: Discussionmentioning
confidence: 99%
“…Rudenko et al 27 showed that two doses of LAIV increased the seroconversion rate to 66% and 72%, according to HI assay and MN assay, respectively. DeZure et al 28 found that the strategy of H7 DNA vaccine prime and H7N9 inactivated vaccine boost would produce higher antibody titers than two-dose non-adjuvanted H7N9 inactivated vaccine. However, in the process of meta-analyzing, one parameter is assessed with the other parameter is fixed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This further emphasizes the need to develop additional correlates of protection for influenza virus infections. Natural infection with H7N9 viruses has been shown to elicit strong humoral responses, including HI titers in humans ( 25 , 30 ), but so far it has not been possible to mimic these responses by vaccination schemes with either live attenuated influenza vaccines (LAIV), inactivated influenza vaccines (IIV), or recombinant H7 HA formulations ( 27 , 28 , 38 , 39 , 50 53 ). Other vaccine candidates, e.g., those based on virus-like particles (VLPs) ( 54 ), could not elicit robust immune responses to H7 either, as shown in past clinical trials in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has become clear that, in the absence of an H7-primed immune system, at least two vaccinations with any H7N9 vaccine are necessary ( 53 ) and that vaccine formulations need to be supplemented with strong adjuvants to boost immune responses to high levels ( 55 ). This is reminiscent of H5 vaccines, which also show lower immunogenicity in humans than seasonal influenza virus vaccines ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%